Phāsit læ samnūan : wannakam mukkhapātha M̄ưang Nakh̨̄on Sī Thammarāt : kānsưksā ch̄œng wikhr̨o - Wimon Damsī (Nangs̄ư chut Nakh̨̄on Sī Thammarāt khadīsưksā, 1997)
Study on folk literature and proverbs of Nakhon Si Thammarat Province, Southern Thailand.